C1-linker region of PARG1 RhoGAP promotes the catalytic recognition fold of RhoA substrate - Zen Kouchi; Masaki Kojima (PLoS ONE, 2025)
PARG1 (ArhGAP29) belongs to a class of F-BAR proteins that contain a GTPase activating (GAP) domain that stimulates the GTP-to-GDP conversion of RhoGTPases. In this study, the substrate-recognition mechanism of human PARG1 was structurally modeled in computational approaches. Docking analysis using HDOCK showed that the predicted RhoGAP domain containing the N-terminal C1 region harbored structural determinants only for RhoA recognition with its catalytic loop and the α4- and α9–10 helices of the GAP domain. Molecular dynamics of wild-type PARG1-RhoA complex revealed that the predicted C1 structure depicted unique interface for the α3 helix of RhoA, leading to stable interaction with the RhoA substrate. Interestingly, RhoA interacted with the C1-GAP domains with missense mutations such as p.Thr622Met (T622M) and p.Ile845Val (I845V) differently, but the several interface residues in the catalytic loop and C-terminal α9-α10 helices were not matched to the known crystallized complexes in molecular dynamics simulation. PARG1 I845V mutant complex was theoretically deduced to disorganize RhoA interfaces and T622M mutation decreased the substrate affinity to 80% of that of WT PARG1 complex. The C-terminal C1 domain that formed a coiled-coil structure in a wild-type specific manner and the loop regions adjacent to the GAP region modulated the corresponding C1 interaction interfaces in RhoA. There were differences in motions of the conserved and variable interface residues among RhoGAP domains that locate in the α9–10 loop and C-terminal α4 and N-terminal α9−10 helices of the GAP domain between WT and mutant RhoGAP-RhoA complexes. The stable RhoA interaction specific to wild-type PARG1 is attributed to the motions of the GAP region including the C1 domain, in contrast to mutant PARG1 GAP domains that tended to disorganize the catalytic complex.